2016
DOI: 10.1016/j.neuron.2016.05.038
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of Prefrontal Cortex-Mediated Slow-Evolving Limbic Dynamics Drives Stress-Induced Emotional Pathology

Abstract: Summary Circuits distributed across cortico-limbic brain regions compose the networks that mediate emotional behavior. The prefrontal cortex (PFC) regulates ultraslow (<1Hz) dynamics across these networks, and PFC dysfunction is implicated in stress-related illnesses including major depressive disorder (MDD). To uncover the mechanism whereby stress-induced changes in PFC circuitry alter emotional networks to yield pathology, we used a multi-disciplinary approach including in vivo recordings in mice and chronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
116
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 114 publications
(131 citation statements)
references
References 49 publications
12
116
1
2
Order By: Relevance
“…3C), such that the amount of immobility exhibited by mice during the second session was lower than expected based on their IL-Thal CFPC. Consistent with the observations that direct PFC stimulation induces an anti-depressant like effect in multiple MDD-related test paradigms (6, 23), these findings suggested that IL-Thal CFPC may reflect a neurophysiological process that induces TST movement. When we used our nCLASP system to recapitulate the spatiotemporal dynamic we identified in IL-Thal circuitry, our findings confirmed that IL-Thal CFPC induces TST-related movement.…”
Section: Discussionsupporting
confidence: 86%
“…3C), such that the amount of immobility exhibited by mice during the second session was lower than expected based on their IL-Thal CFPC. Consistent with the observations that direct PFC stimulation induces an anti-depressant like effect in multiple MDD-related test paradigms (6, 23), these findings suggested that IL-Thal CFPC may reflect a neurophysiological process that induces TST movement. When we used our nCLASP system to recapitulate the spatiotemporal dynamic we identified in IL-Thal circuitry, our findings confirmed that IL-Thal CFPC induces TST-related movement.…”
Section: Discussionsupporting
confidence: 86%
“…This is similar to a report that even a single episode of stress can weaken functional connectivity between the two areas measured by resting state fMRI (Liang et al, 2014). Indeed, such stress-induced disruptions in prefrontal-to-amygdala connectivity is also known to affect social interaction and anxiety-related behaviors in rodents (Adhikari et al, 2015;Hultman et al, 2016). Finally, it is interesting to note that the same chronic stress paradigm was previously shown to strengthen functional connectivity from the amygdala to the hippocampus (Ghosh et al, 2013), which undergoes stress-induced deficits similar to the mPFC (Arnsten, 2015;Chattarji et al, 2015;McEwen and Morrison, 2013).…”
Section: Resultssupporting
confidence: 88%
“…We then sought to determine whether the same ACC→BLA circuit was involved in a more ethologically-relevant task – the avoidance of aggressive and potentially threatening animals (Hultman et al, 2016). Naïve observer mice were injected with NpHR or eYFP bilaterally in the ACC and implanted with optical fibers over the BLA, and the ACC→BLA projection was inhibited while the observer witnessed the interaction of a familiar demonstrator mouse and an aggressive CD-1 mouse for two 3-minute sessions (Figure 7A).…”
Section: Resultsmentioning
confidence: 99%